An animated dictionary for hearing-impaired students in Thailand - Wicha S. (2017)
As English increasingly becomes the international language, many ministerial and educational organisations have identified the need to improve the competence of Thai students in speaking English. While there is significant research devoted to developing software tools to support the teaching of English as a second language, they are mostly concerned with adult learners. This project focuses on addressing the need to improve the teaching of English as a second language to primary school children with hearing impairments. This paper presents the development of an educational software tool referred to as the Total Communication with Animation Dictionary (TCAD), which supports learners in the acquisition and retention of new English lexical knowledge and is based on the theoretical approaches of Total Communication and situated learning. A series of experiments was undertaken to evaluate the effectiveness of the TCAD in improving vocabulary acquisition and retention. Early results are promising with increased learner engagement and performance compared with traditional approaches. © 2012 NASEN.